1980
DOI: 10.2134/jeq1980.00472425000900020019x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Simulated Rainfall on Residual Bacteria and Virus on Grass Treated with Sewage Sludge

Abstract: The influence of simulated rainfall on the survival of fecal coliforms and coliphage on bermudagrass (Cynodon dactylon L.) and rhodesgrass (Cholris gayana Kunth.) following applications of liquid digested sludge containing varying amounts of solids was investigated using the most probable number and plaque count techniques, respectively. The numbers of coliphage on the grass decreased rapidly with drying time and at 48 hours after application none were detected in any of the treatments. Rainfall was effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In one previous study, Brown et al (1980) (Brown et al, 1980). Rotavirus SA-11 concentrations decreased more rapidly than poliovirus both in summer and winter.…”
Section: Discussionmentioning
confidence: 75%
“…In one previous study, Brown et al (1980) (Brown et al, 1980). Rotavirus SA-11 concentrations decreased more rapidly than poliovirus both in summer and winter.…”
Section: Discussionmentioning
confidence: 75%
“…This range is in agreement with other studies in different matrices (Gantzer et al, 2001;Hurst et al, 1980) though a more rapid decay has also been found. Brown (1980) showed that coliphages were not detectable after 48 h in grass after sludge application due to the drier conditions. E. fecalis persisted much better than E. coli and was less affected by temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The die-off time is usually expressed as a decimal reduction (T 90 ) or as the time after which organisms are no longer detectable (total die-off). The latter may vary between days and several months for viruses, bacteria and parasitic protozoa (Badawy et al, 1990;Brown et al, 1980) while helminth eggs may persist for years (O'Donnell et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that enteric pathogens survive wastewater treatment process in low numbers (Sidhu and Toze ) and then, if introduced to soil at the time of biosolids application, subsequent contamination onto plant leaves may occur during the rainfall events (Brown et al . ; Boyer ). If this was to occur in food grain crops, contaminated grains and fodder could potentially transmit diseases to humans and livestock at consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, pathogens may survive better under certain conditions such as in the shade or under increased moisture content, usually between the leaves and stems of the plants (Brown et al . ; Lindow and Brandl ; Ibekwe et al . ).…”
Section: Introductionmentioning
confidence: 99%